A bibliometric analysis of the 100 most influential papers on peritoneal dialysis. Issue 47 (20th November 2020) - Yuan, Xinke; Li, Hui; Zhou, Luting; Huang, Yinghong
Abstract: Background: We aimed to identify the 100 most cited articles published on peritoneal dialysis (PD) and analyze their characteristics to provide information on the achievements and developments of PD research over the past decades. Methods: The Science Citation Index Expanded (SCIE) in the Web of Science Core Collection was comprehensively searched from 2000 to 2018, using the keywords "Peritoneal dialysis" or "Dialyses, Peritoneal" or "Dialysis, Peritoneal" or "Peritoneal Dialyses". The top 100 cited articles were retrieved by reading titles and abstracts. Significant information was further elicited, including the authors, journals, countries, institutions, and publication year. Results: The United States was the most productive country (n = 51), Li Pkt published the highest number of papers (n = 7), the Journal of the American Society of Nephrology produced the highest number of contributions (n = 28), and Baxter International Inc., the University of California System, and the University of Toronto were the institutions with the highest number of articles (n = 10). Conclusions: This is the first bibliometric study to identify the most influential papers in PD research. This report describes the major changes and advances in research regarding PD as a guide for writing a citable article.